Pesticide residues in blackberries (Rubus glaucus Benth.) in the Valle del Cauca, Colombia - Lagos-Alvarez, Yorley Beatriz (2022)
Introduction. The blackberry (Rubus glaucus) is a fruit very susceptible to contamination by pesticide residues during its production stage. For this reason, the analysis of pesticide residues in this fruit is important to promote processes that contribute to ensure its quality and safety. Objective. To analyze the pesticide residues in blackberry (Rubus glaucus) fruits obtained from production areas and wholesale markets in Valle del Cauca. Materials and methods. During the second semester of 2020 and the first semester of 2021, fifteen samples from two wholesale markets and fifteen samples of three production areas of Valle del Cauca were analyzed through a multi-residue analysis of pesticides by gas chromatography coupled with a mass selective detector (GC - MSD) and liquid chromatography with mass-to-mass spectrometry (LC-MS / MS). For this, the QuEChERS method was used and, in addition, an analysis of total dithiocarbamates by carbon disulfide (CS2) generation was performed. Results. Eight active ingredients were found in the production areas, of which four of them exceeded the maximum residue limits: chlorpyrifos, carbendazim, mandipropamid, and difenoconazole. In the market places, fourteen active ingredients were determined, which five exceeded the maximum residue limits: carbendazim, iprodione, tebuconazole, dimethomorph, and difenoconazole. Conclusion. These findings reflect the high residual pesticide residues in ready-to-eat blackberries and suggest the need for follow-up processes to help ensure the safety of the fruit throughout the production chain.